Associations Between Prediagnostic Concentrations of Circulating Sex Steroid Hormones and Liver Cancer Among Postmenopausal Women. Issue 2 (25th August 2020) - Petrick, Jessica L.; Florio, Andrea A.; Zhang, Xuehong; Zeleniuch‐Jacquotte, Anne; Wactawski‐Wende, Jean; Van Den Eeden, Stephen K.; Stanczyk, Frank Z.; Simon, Tracey G.; Sinha, Rashmi; Sesso, Howard D.; Schairer, Catherine; Rosenberg, Lynn; et al.
Abstract : Background and Aims: In almost all countries, incidence rates of liver cancer (LC) are 100%‐200% higher in males than in females. However, this difference is predominantly driven by hepatocellular carcinoma (HCC), which accounts for 75% of LC cases. Intrahepatic cholangiocarcinoma (ICC) accounts for 12% of cases and has rates only 30% higher in males. Hormones are hypothesized to underlie observed sex differences. We investigated whether prediagnostic circulating hormone and sex hormone binding globulin (SHBG) levels were associated with LC risk, overall and by histology, by leveraging resources from five prospective cohorts. Approach and Results: Seven sex steroid hormones and SHBG were quantitated using gas chromatography/tandem mass spectrometry and competitive electrochemiluminescence immunoassay, respectively, from baseline serum/plasma samples of 191 postmenopausal female LC cases (HCC, n = 83; ICC, n = 56) and 426 controls, matched on sex, cohort, age, race/ethnicity, and blood collection date. Odds ratios (ORs) and 95% confidence intervals (CIs) for associations between a one‐unit increase in log2 hormone value (approximate doubling of circulating concentration) and LC were calculated using multivariable‐adjusted conditional logistic regression. A doubling in the concentration of 4‐androstenedione (4‐dione) was associated with a 50% decreased LC risk (OR = 0.50; 95% CI = 0.30‐0.82), whereas SHBG was associated with a 31% increased risk (OR = 1.31; 95% CI = 1.05‐1.63). Examining histology, a doubling of estradiol was associated with a 40% increased risk of ICC (OR = 1.40; 95% CI = 1.05‐1.89), but not HCC (OR = 1.12; 95% CI = 0.81‐1.54). Conclusions: This study provides evidence that higher levels of 4‐dione may be associated with lower, and SHBG with higher, LC risk in women. However, this study does not support the hypothesis that higher estrogen levels decrease LC risk. Indeed, estradiol may be associated with an increased ICC risk.